A comparative study for some phases of the menstrual cycle hormones and its relationship to performance of the female shooters of air guns - Natiq, Ghisoun (Journal of Physical Education, 2015)
The physiological and biological changes that recur in her body almost every month through a complete cycle called “Menstrual cycle” so that the efforts of their obligations during the competition period will be full of negative impacts whether it was Functional or psychological or organic aspects, this is due to the different rate of the discharge of female hormones during the period, competitive atmosphere may play an important role and here is the importance of the research which is A comparative study for some phases of the menstrual cycle hormones and its relationship to performance of the female shooters of air guns. The research problem is to identify the rates of secretion of estrogen and progesterone, and secretion rates during phases of the menstrual cycle. The aim of the study: 1- A comparative study of achievement in each of the formative phase and endocrine for female shooters of air guns. 2- Identify the relationship between some phases of the menstrual cycle hormones and achievement. The researcher chooses (8) female shooters specialized in (air gun- air pistol), They represent the original community 100%, the shooters period date was nearly so that two players were ruled out then the sample number became six shooters. The researcher chose the sample of players in the same month of their period and the date of their training camping, which is the time before the competition. These camps present real competition where the shooters were involved, then they have a blood test to identify the rates of the two hormones estrogen and progesterone during two phases of the menstrual cycle, they are formative and endocrine phase, after their entry in the achievement test. The researcher concluded: Different level of achievement in each of the formative and endocrine phase depending on the levels of estrogen and progesterone The researcher recommends that: The importance of focusing on physiological and biological aspects concerning the sport woman, In the forefront of the aspects concerning the levels of female hormones and follow-up through the stages of training